An introduction to practical formal methods using temporal logic - Fisher, Michael 1962- (Wiley, 2011)
This book provides an introduction to formal methods based on temporal logic, describing techniques for testing and developing complex computational systems. It starts with a full introduction to the subject and then goes into more detail, covering the basics of temporal logics in order to give the reader a firm basis on which to progress further.
Includes bibliographical references and index. - Print version record
Keywords: Temporal automata; Logic, Symbolic and mathematical; Automates temporels; Logique symbolique et mathématique; MATHEMATICS; Infinity; MATHEMATICS; Logic